BENTUK DAN STRUKTUR NOVEL 1984 KARYA ORWELL, G. - Dhivia Purnama Arsiladeva; Syahla Fatia Zahra; Nurholis Nurholis (Cahaya Ilmu Bangsa Institute, 2024)
Abstract This research explains the forms and structures in the novel 1984 by George Orwell. The novel presents a dystopian tale set against the backdrop of a totalitarian regime, where the Communist Party, led by Big Brother, exercises strict control over every aspect of society. The story centers on Winston Smith, a low-ranking Party member who works at the Ministry of Truth, where he is tasked with altering historical records to support the Party's narrative. Feeling oppressed by pervasive surveillance and relentless propaganda, Winston secretly rebels by seeking truth and individual freedom. In his quest, he forms a forbidden relationship with Julia, a fellow Party member, and together they savor moments of intimacy and resistance. However, their rebellion is ultimately crushed by the Party's machinery of control. Winston is captured, tortured, and reprogrammed to fully align with the Party's ideology. The novel explores themes of power, identity, and the malleability of truth while highlighting the dangers of surveillance, language manipulation, and the loss of personal autonomy. Through its grim portrayal of a world devoid of individuality and freedom, 1984 serves as a profound warning against totalitarianism and the consequences of unchecked power. Keywords: form, structure, 1984, George Orwell, dystopia, totalitarianism, Big Brother, strict control, Winston Smith, Ministry of Truth. Abstract Penelitian ini berisi tentang penjelasan bentuk dan struktur dalam novel 1984 karya George Orwell. Novel ini berisi tentang sebuah kisah distopia yang berlatar belakang rezim totaliter, dimana Partai Komunis yang dipimpin oleh Big Brother melakukan kontrol ketat terhadap setiap aspek kehidupan masyarakat. Cerita ini berfokus pada Winston Smith, seorang anggota Partai dengan pangkat rendah yang bekerja di Kementerian Kebenaran, di mana dia bertugas mengubah catatan sejarah untuk mendukung narasi Partai. Merasa tertekan oleh pengawasan yang mengikat dan propaganda yang tiada henti, Winston secara diam-diam memberontak dengan mencari kebenaran dan kebebasan individu. Dalam upayanya, dia menjalin hubungan terlarang dengan Julia, sesama anggota Partai, dan mereka menikmati momen-momen keintiman dan perlawanan. Namun, pemberontakan mereka pada akhirnya dihancurkan oleh mesin kontrol Partai. Winston ditangkap, disiksa, dan diprogram ulang agar sepenuhnya sesuai dengan ideologi Partai. Novel ini menyelidiki tema kekuasaan, identitas, dan fleksibilitas kebenaran, serta menyoroti bahaya pengawasan, manipulasi bahasa, dan hilangnya otonomi pribadi. Melalui gambaran suram tentang dunia yang kehilangan individualitas dan kebebasan, 1984 menjadi peringatan yang mendalam terhadap totalitarianisme dan konsekuensi dari kekuasaan yang tidak terkendali. Keywords: bentuk, struktur, 1984, George Orwell, distopia, totalitarianisme, Big Brother, kontrol ketat, Winston Smith, kementerian kebenaran.